Diffusive breast diseases: a new vector of targeted therapy - A E Protasova; E N Vandeeva (IP Berlin A.V., 2017)
The article describes the review of literature risk factors for fibrocystic disease (FCD), the role and place of individual risk factors such as mammographic density and cyclic mastalgia. The evaluation of significant clinical symptoms as a risk factor for breast cancer (BC) was made. The modern possibilities of diagnostics of FCD are considered. The modern recommendations on medical tactics are given. The pathogenetic treatment of FCD aimed at preventing breast cancer is described; The use of a Progestogel® drug for the treatment of FCD and breast cancer prophylaxis.